Clinical–Pathological Agreement in Dementing Disorders: Embracing the Complexity - Huey, Edward D. (Tremor Other Hyperkinet Mov (N Y), 2014)
In Response to: Giorelli M, Losignore NA, Bagnoli J, et al. The progression of posterior cortical atrophy to corticobasal syndrome: Lumping or splitting neurodegenerative diseases? Tremor Other Hyperkinet Mov. 2014; 4. doi: 10.7916/D81G0JCQ